Docking Interaction of Protein Tyrosine Phosphatase and Complex Chromium(III) Nicotinate Compounds - Yuli Ambarwati; MA Martoprawiro; I Mulyani; Ismunandar Ismunandar; D Onggo (Syarif Hidayatullah State Islamic University, 2017)
Docking simulation is important in the process of drug design, mainly used for the prediction of interactions receptor(protein)–substrate. This study aims to understand the interaction between Chromium(III) nicotinate [Cr(O-nic)2(OH-) (H2O)3] and [Cr(N-nic)2(OH-)(H2O)3] with the position of trans and cis as a substrate with receptors Protein Tyrosine Phosphatase(PTP). The chromium(III) nicotinic complexes an antidiabetic supplement that have been demonstrated in vitro, to determine the role of chromium(III) nicotinic as a supplement antidiabetic learned through the docking mechanism. The optimization of the complex structure of chromium(III) nicotinic using Gaussian 09, the docking process is performed using Autodock Vina. The docking results showed that trans[Cr(O-nic)2(OH-)(H2O)3] position interact with Leu13, Gly14, Cys17, Arg18, Trp49 and Asn50 with the interaction energy is -6.5 kcal/mol. As for the structure model cis[Cr(O-nic)2(OH-)(H2O)3] have -6.1 kcal/mol interaction energy and the amino acid Ile16, Trp49, Asn50, Arg53, Asp56 and Tyr131. The similar things at modelof N-coordinated to Cr withtrans[Cr(N-nic)2(OH-)(H2O)3] position interact with amino acids Leu13, Ser47, Trp49, Asn50 and Tyr131 the interaction energy is -6.5 kcal/mol. The ONIOM calculation showed the bond between the complexes of chromium(III) nicotinic with PTP is hydrogen bonding. The best interactions with the receptor are the structure model trans[Cr(O-nic)2(OH-)(H2O)3] with the lowest interaction energy interaction.